2018
DOI: 10.1038/s41522-018-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Fighting biofilms with lantibiotics and other groups of bacteriocins

Abstract: Biofilms are sessile communities of bacteria typically embedded in an extracellular polymeric matrix. Bacterial cells embedded in biofilms are inherently recalcitrant to antimicrobials, compared to cells existing in a planktonic state, and are notoriously difficult to eradicate once formed. Avenues to tackle biofilms thus far have largely focussed on attempting to disrupt the initial stages of biofilm formation, including adhesion and maturation of the biofilm. Such an approach is advantageous as the concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
120
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(126 citation statements)
references
References 176 publications
(199 reference statements)
2
120
0
4
Order By: Relevance
“…Bacteriocins Pep 5 and epidermin produced by Staphylococcus epidermidis both demonstrated an inhibitory action against the adhesion of Staphylococcus species to the surfaces of silicon catheters [36]. Additionally, nisin has been reported to possess biofilm penetrating abilities potentially making it a useful tool in preventing or eradicating biofilm communities [40] on invasive medical devices. Preliminary investigative studies also suggest possible uses of nisin as antibacterial coatings on implantable medical devices [40].…”
Section: Infectious Diseasementioning
confidence: 99%
See 3 more Smart Citations
“…Bacteriocins Pep 5 and epidermin produced by Staphylococcus epidermidis both demonstrated an inhibitory action against the adhesion of Staphylococcus species to the surfaces of silicon catheters [36]. Additionally, nisin has been reported to possess biofilm penetrating abilities potentially making it a useful tool in preventing or eradicating biofilm communities [40] on invasive medical devices. Preliminary investigative studies also suggest possible uses of nisin as antibacterial coatings on implantable medical devices [40].…”
Section: Infectious Diseasementioning
confidence: 99%
“…Additionally, nisin has been reported to possess biofilm penetrating abilities potentially making it a useful tool in preventing or eradicating biofilm communities [40] on invasive medical devices. Preliminary investigative studies also suggest possible uses of nisin as antibacterial coatings on implantable medical devices [40]. In vivo animal studies have demonstrated the efficacy of lantibiotics for preventing and treating infectious disease.…”
Section: Infectious Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Bacteriocins could inhibit “quorum sensing” and therefore suppressing biofilm formation (Chopra, Singh, Jena, & Sahoo, ; Algburi et al., ); biofilms are polymeric matrix produced by microorganisms more of all related with pathogenic ones and recognized as a public health problematic (Simões, Simoes, & Vieira, ). Once biofilms are established by a microbial community, removing them is more difficult than preventing their formation; bacteriocins could work as a preventive measure for preventing biofilm formation in many industries (Mathur et al., ).…”
Section: Bacteriocins: Technological Applicationmentioning
confidence: 99%